Association of lysophosphatidic acids with cerebrospinal fluid biomarkers and progression to Alzheimer’s disease - Ahmad, Shahzad; Orellana, Adelina; Kohler, Isabelle; Frölich, Lutz; de Rojas, Itziar; Gil, Silvia; Boada, Mercè; Hernández, Isabel; Hausner, Lucrezia; Bakker, Margot H. M.; Cabrera-Socorro, Alfredo; Amin, Najaf; et al. (Alzheimer's research & therapy, 2020)
Lysophosphatidic acids (LPAs) are bioactive signaling phospholipids that have been implicated in Alzheimer’s disease (AD). It is largely unknown whether LPAs are associated with AD pathology and progression from mild cognitive impairment (MCI) to AD.